Modular low-cost 3D printed setup for experiments with NV centers in diamond. (1st May 2023) - Stegemann, Jan; Peters, Marina; Horsthemke, Ludwig; Langels, Nicole; Glösekötter, Peter; Heusler, Stefan; Gregor, Markus
Abstract: With the advent of quantum technology, the need for affordable, flexible and robust laboratory experiments not only for students, but also at high school level is increasing. Here, for the first time, we report on a simple modular 3D printed low-cost (<250 €) setup which fulfils these needs for quantum sensing experiments based on nitrogen-vacancy centers in diamonds. Commercially available setups for optically detected magnetic resonance in microdiamonds used as quantum sensor for magnetic fields are not only beyond the reach of any high school (>10 000 €), but also have shortcomings from a didactical point of view, as all the components of the setup are hidden within a 'black box', doomed to be successful 'plug and play'. In contrast, our open-source experimental kit consists of optical components that are placed inside 3D printed open-framed cubes, that can be arranged freely on a grid. This modular and flexible design can provide an inquiry-based learning experience both at undergraduate and high school level.